European survey on national harmonization in clinical research. Issue 2 (21st February 2020) - Magnin, Annette; Iversen, Valentina Cabral; Calvo, Gonzalo; Čečetková, Beata; Dale, Ola; Demlová, Regina; Blaskó, György; Keane, Fionnuala; Kovacs, Gabor L.; Levy‐Marchal, Claire; Monteiro, Emilia C.; Palmisano, Lucia; et al.
Abstract: Background: Clinical trials remain key to the development of evidence‐based medical practice. However, they are becoming increasingly complex, mainly in a multinational setting. To address these challenges, the European Union (EU) adopted the Clinical Trial Regulation EU No. 536/2014 (CTR). Once in force, the CTR will lead to more consistent rules and simplification of procedures for conducting clinical trials throughout the EU. Existing harmonization initiatives and "research infrastructures" for clinical trials may facilitate this process. This publication offers a snapshot of the current level of harmonization activities in academic clinical research in Europe. Methods: A survey was performed among the member and observer countries of the European Clinical Research Infrastructure Network (ECRIN), using a standardized questionnaire. Three rounds of data collection were performed to maximize completeness and comparability of the received answers. The survey aimed to describe the harmonization of academic clinical research processes at national level, to facilitate the exchange of expertise and experience among countries, and to identify new fields of action. Results: Most scientific partners already have in place various working groups and harmonization activities at national level. Furthermore, they are involved in and open to sharing their know‐how and documents. Since harmonization was mainly a bottom‐up approach up until now, the extent and topics dealt with are diverse and there is only little cross‐networking and cross‐country exchange so far. Conclusions: Currently, the ECRIN member countries offer a very solid base and collaborative spirit for further aligning processes and exchanging best practices for clinical research in Europe. They can support a smooth implementation of the EU CTR and may act as single contact with consolidated expertise in a country.